Giant leiomyosarcoma of the inferior vena cava necessitating extended liver resection: A case report and review of the literature. Issue 6 (22nd June 2021) - Silverman, Jacob; Pencovich, Niv; Mayer, Chen; Volkov, Alexander; Eshkenazi, Rony; Nachmany, Ido
Abstract: Leiomyosarcoma of the inferior vena cava (IVC) is a rare malignant tumour of smooth muscle origin. It commonly presents with non-specific symptoms including abdominal pain, distention, and lower extremity edema. Surgical resection with macroscopically clear margins is the only potential curative treatment for the disease. Here we present the case of a previously healthy 38-year-old woman with a subacute one-month increase of a four-year slowly progressive right sided abdominal pain and back pain. Imaging revealed a 14.5x12x15cm mass in the right hepatic lobe causing mass effect on adjacent abdominal and retroperitoneal organs, and involving the retrohepatic IVC. En-bloc resection of the right hemi-liver, most of segment four, the caudate lobe, and approximately a 10 cm section of the retrohepatic IVC, along with IVC reconstruction, was performed. Histologic examination revealed the diagnosis of a high grade leiomyosarcoma.